Pericarditis Caused by Beta-Lactamase-Producing Haemophilus Influenzae: Report of Two Cases in Adults and Review of the Literature - Greenberg, Daniel (1986)
Two adult patients with pericarditis caused by beta-lactamase producing Haemophilus influenzae are reported and their management reviewed. Both had pharyngitis, epiglottitis, pneumonia, empyema, or septicemia and were cured with antimicrobics and pericardial drainage (one by catheter and one by surgery). Eleven previously reported cases of pericarditis caused by Haemophilus influenzae are also reviewed. In reviewing this rare cause of bacteria pericarditis, it is important to recognize the antibiotic resistance profile, the incidence of pericardial tamponade, and the use of surgical drainage. Antibiotic selection for this organism is also discussed, as well as the importance of biotyping. (Texas Heart Institute Journal 1986; 13:297-303)